Outcomes of Pediatric Patients With Sepsis Related to Staphylococcus aureus and Methicillin-Resistant Staphylococcus aureus Infections Requiring Extracorporeal Life Support: An ELSO Database Study - Foster, Cortney; Bagdure, Dayanand; Custer, Jason; Holloway, Adrian; Rycus, Peter; Day, Jenni; Bhutta, Adnan (Frontiers in Pediatrics, 2021)
Background: Extracorporeal membrane oxygenation (ECMO) is increasingly utilized for pediatric sepsis unresponsive to steroids and inotropic support. Outcomes of children with sepsis are influenced by the type of pathogen causing their illness. Objective: To determine if the outcomes of children with Staphylococcus aureus sepsis receiving ECMO differed according to microbial sensitivity (Methicillin-resistant Staphylococcus aureus [MRSA] vs Methicillin-sensitive Staphylococcus aureus [MSSA]). Methods: Retrospective case-matched cohort study of children (0-<18yrs) with Staphylococcus aureus sepsis reported to the ELSO registry from more than 995 centers. Inclusion criteria were age 0 to 18 years, laboratory diagnosis of Staphylococcal infection, clinical diagnosis of sepsis, and ECMO deployment. Exclusion criteria were no laboratory diagnosis of Staphylococcal infection. We compared patient demographics, pre-ECMO management and outcomes of those with MRSA vs MSSA using Chi-Square test, with independent samples t-test used to test to compare continuous variables. Results: In our study cohort of 308 patients, 160 (52%) had MSSA and 148 (48%) MRSA with an overall survival rate of 41.5%. There were no differences in the age group (p 0.76), gender distribution (p 0.1) or racial distribution (p 0.58) between the two groups. There were 91 (56.8%) deaths in the MSSA group and 89 (60.1%) deaths (p 0.56) in the MRSA group. Duration on ECMO (p 0.085) and the time from intubation to ECMO (p 0.37) were also similar in the two groups. Survival with MSSA sepsis and MRSA sepsis did not improve significantly over the 20 years evaluated despite an increase in ECMO utilization. Conclusion: In this multi-center retrospective study, there were no differences in outcomes for children receiving ECMO support with Staphylococcus aureus sepsis according to microbial methicillin sensitivity. There was no significant increase in survival among patients with MRSA and MSSA infections receiving ECMO in the last 20 years.